An Archaeological Study of Early Farming Settlements on Iresi Hills - Olusegun Akanni Opadeji (Yoruba Studies Review)
Recent Investigation of an archaeological site in southwest Nigeria during the Late Stone Age revealed additional information about the cultural development of the area. On Iresi Hills two rock shelters (Ajaye and Cherubim & Seraphim) were investigated in two seasons from 2017 to 2018 during which pottery, ground stone axes and microlithics were excavated. Although there is no clear break in the stratigraphy, the findings show clear demarcation between two cultural layers. The upper layer contains pottery, microlithics and ground stone axes, and ochre while the lower layer is characterized by microlithics only. The site presented a date of about Cal 5653 BP which coincides with a short dry period in the area. Tis paper reports the occupation in Iresi, in southwest Nigeria with a view to fill the gap in the chronology and to interrogate the evidence for Late Stone Age in terms of the culture that existed in between 12000YBP of Iwo Eleru and 2000YBP of Itaakpa and the influence of a change in environment of southwest Nigeria and West Africa in general.